E-Service Quality Hotel Pangeran Pekanbaru Pada Website Traveloka - Wardiyanti, Ervina; Purwandani, Intan (JURNAL MASTER PARIWISATA; Volume 08, Nomor 01, Juli 2021DO - 10.24843/JUMPA.2021.v08.i01.p09, 2021)
Hotel Pangeran Pekanbaru is a 4-star hotel in Pekanbaru City which uses several Online Travel Agent (OTA) companies as online reservation media, with one of the highest reservation comes from Traveloka. The purpose of this study is to assess the electronic quality service of Traveloka’s website as an online reservation media at Hotel Pangeran Pekanbaru. The six dimensions of e-service quality by Tsang et al. (2010) include: (1) Website Function; (2) Quality and Information Content; (3) Need Fulfillment and Responsiveness; (4) Safety and Security; (5) Appearance and Presentation; and (6) Customer Relationships are implemented as a measure of the quality of an OTA's electronic service. This research is a descriptive quantitative study using data collection methods of survey and online questionnaire as a research tool. Online questionnaires were distributed to 100 guests of Hotel Pangeran Pekanbaru who had made online reservations through the Traveloka website. The results of this study indicate that the respondents' perceptions of Traveloka website’s e-service quality as an online reservation media for Hotel Pangeran Pekanbaru were classified as "high" with an average score of 3.56. Although the overall value of e-service quality on the Traveloka website is classified as "high", at the e-service quality value from the respondent's profile perspective, there is a minority group of 1% who answered that the quality of electronic services was in the "medium" category. Keywords: electronic service quality, online travel agent, Traveloka, online reservation, online booking